On Parody - Fredericksen, Don (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
<span style="font: 10px/normal Verdana, Arial, Helvetica, sans-serif; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; word-spacing: 0px; float: none; display: inline !important; white-space: normal; widows: 1; font-size-adjust: none; font-stretch: normal; background-color: #ffffff; -webkit-text-stroke-width: 0px;">The essay consists of a series of examples of parody, and of statements regarding the nature and functions of parody. One is allowed to wonder if the form of the essay parodies obsessive-compulsive thought. Parody is taken to be a form of irony within the verbal, visual, and acoustical arts. As well, the claim is made that it is often unwittingly manifested in personal behavior, and in theories of human nature upon which forms of utopian thought and social engineering are based. Examples are drawn from film, painting, literature and literary criticism, psychotherapy, teaching, the writing of history, social engineering, and jokes. Parody is taken to be a major means for combating the corruption of consciousness in both its personal and communal forms.